Intake of nutritional ergogenic aids among Malaysian team sport athletes - Ling, Li Keat; Abu Saad, Hazizi; Chee, Huei Phing (Malaysia Association of Research and Education for Educators, 2017)
Substantial evidence denotes the ignorance of athletes concerning their required nutritional practices, as disclosed by the extensive use of nutritional ergogenic aids to enhance performance. There has been extensive information on the use of nutritional ergogenic aids among athletes in Western countries. However, little is known about the nutritional ergogenic aids used among Malaysian athletes. This study was to evaluate the intake of nutritional ergogenic aids among team sport athletes in the National Sports Institute, Malaysia. A total of 120 team sport athletes out of 400 athletes in the National Sports Institute, Malaysia were invited to participate; they consisted of football, hockey, and Sepak Takraw athletes. There was a significant moderate positive correlation between age (r=0.415, p=0.01) and year of participation (r=0.446, p=0.01) with the number of nutritional ergogenic aids taken by the subjects. There was a significant weak positive correlation between physical activity level (r=0.231, p=0.05) and the number of nutritional ergogenic aids taken by the subjects. In addition, there was a significant association between gender and the nutritional ergogenic aids used among the subjects (χ2=18.207, p<0.001). There was a significant association between type of sports and nutritional ergogenic aid intake of the subjects (χ2=31.264, p<0.001). The study indicated that the prevalence of nutritional ergogenic aids used among team sport athletes in the National Sports Institute, Malaysia was lower (59.7%) when compared to previous studies conducted in Western countries, and even in Singapore, with sports food and drinks (45.5%) as the most commonly used nutritional ergogenic aids, followed by vitamins and minerals (27.3%) and protein (24.7%).